2019
DOI: 10.21203/rs.2.13228/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative metabolome analysis of serum changes in sheep under overgrazing or light grazing conditions

Abstract: Background Overgrazing is a primary contributor to severe reduction in forage quality and production in Inner Mongolia, leading to extensive ecosystem degradation, sheep health impairment and growth performance reduction. However, no clear information about the effect of overgrazing on sheep health and nutritional metabolism is available because no objective serum biomarkers are currently evident. We hereby hypothesize that reduced sheep growth performance under overgrazing conditions would be associated with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…found that serum GLU levels in overgrazed were significantly lower than those in the lightly grazed group [11] , this is consistent with that we found the serum GLU content is more in SSMF group. And Grigol et al in comparing the effects of different grazing times on the health status of dairy cows, found that an increase in the time spent on grazing led to a decrease in the BUN levels of the animals [12] .…”
Section: Correlation Analysis Of Gut Microorganisms With Metabolitessupporting
confidence: 91%
“…found that serum GLU levels in overgrazed were significantly lower than those in the lightly grazed group [11] , this is consistent with that we found the serum GLU content is more in SSMF group. And Grigol et al in comparing the effects of different grazing times on the health status of dairy cows, found that an increase in the time spent on grazing led to a decrease in the BUN levels of the animals [12] .…”
Section: Correlation Analysis Of Gut Microorganisms With Metabolitessupporting
confidence: 91%